Impact of a Remote Monitoring Programme Including Lifestyle Education Software in Type 2 Diabetes: Results of the Educ@dom Randomised Multicentre Study - Turnin, Marie-Christine; Gourdy, Pierre; Martini, Jacques; Buisson, Jean-Christophe; Chauchard, Marie-Christine; Delaunay, Jacqueline; Schirr-Bonnans, Solène; Taoui, Soumia; Poncet, Marie-France; Cosma, Valeria; Lablanche, Sandrine; Coustols-Valat, Magali; et al. (Diabetes therapy, 2021)
Introduction Telemonitoring in type 2 diabetes (T2D) is mainly based on glucose monitoring. A new type of connected device which routinely gathers data on weight, physical activity and food intake could improve patients’ diabetes control. The main aim of this study was to assess the efficacy of an at-home interventional programme incorporating such devices and lifestyle education software on diabetes control, i.e., change in HbA1c, compared to standard care. Methods This multicentre study randomly assigned 282 people with T2D to either a telemonitoring group (TMG) or a control group (CG) for a 1-year intervention period. While routine follow-up was maintained in the CG, TMG subjects were provided with interactive lifestyle educational software (with artificial intelligence algorithms) and connected objects (blood glucose meters, scales and actimeters) for use in their own homes and were remotely monitored by their diabetologists. Changes in HbA 1c were compared between groups using a mixed linear model. Results The mean HbA 1c dropped from 7.8 ± 0.8% (62 mmol/mol) to 7.4 ± 1.0% (57 mmol/mol) in the TMG and from 7.8 ± 0.8% (62 mmol/mol) to 7.6 ± 1.0% (60 mmol/mol) in the CG, resulting in an intergroup difference of − 0.16 ( p = 0.06) in favour of TMG, after adjustment for confounding factors. Within TMG, the decrease in HbA 1c was greater in frequent users: − 0.23% ( p = 0.03) in the case of connections to telemonitoring synthesis above the median and − 0.21% ( p = 0.05) in the case of connections to tele-education software above the median compared to the CG. Significant weight loss was observed in the TMG but only in women ( p = 0.01). Findings The EDUC@DOM telemonitoring and tele-education device did not highlight a significant decrease in HbA1c levels compared to routine management although a slight, albeit significant improvement in glycaemic control was observed in the frequent user subgroup as well as significant weight loss but only in women. A high level of satisfaction with the connected device was recorded amongst all participants. Trial Registration This trial was registered in the Clinical Trials Database on September 27, 2013, under no. NCT01955031 and bears ID-RCB number 2013-A00391-44.